Feeding and oral processing behaviors of two colobine monkeys in Tai Forest, Ivory Coast. Issue 98 (September 2016) - McGraw, W. Scott; van Casteren, Adam; Kane, Erin; Geissler, Elise; Burrows, Brittany; Daegling, David J.
Abstract: We collected frequency data on oral processing behaviors during feeding in habituated groups of Western red colobus, Piliocolobus badius, and Western black and white, Colobus polykomos, ranging in the Ivory Coast's Tai National Park. During the sampling period, the diet of red colobus consisted of approximately 75% leaves compared to approximately 47% leaves and buds in black and white colobus. Black and white colobus chewed more frequently per ingestive event than did red colobus. Black and white colobus also employed their anterior teeth much more frequently than did red colobus, a difference attributed to the frequent consumption by C. polykomos of Pentaclethra macrophylla seeds and pods. A material analysis of these food items reveals that both the seed coating and seed flesh are quite soft; however, the pod housing the seeds is very tough. We argue that the pod's toughness, geometry, and fiber orientation collectively result in a food that is very difficult to process, resulting in long handling times and frequent, aggressive use of the incisors. We compare these data with those collected on another Tai primate—the sooty mangabey, Cercocebus atys —and demonstrate that during feeding, both colobine species use their incisors less than the mangabey, but that the cercopithecine chews less than either colobine. Combining data on oral processing behaviors with those on the material properties of items being ingested should lead to more informed interpretations of dentognathic morphology.